Using Mathematica & Matlab For CAGD/CAD Research Education. - R., Gobinathan; Md. Ali, Jamaludin (2005)
In CAGD/CAD research and education, users are involved with development of mathematical algorithms and followed by the analysis or the resultant algorithm.